(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
The COVID-19 pandemic started in early December 2019. It appeared first time in People Republic of China and spread worldwide infecting more than 50 million people till today. The disease caused more than one million deaths worldwide and still the threat is present. The acute pneumonia resulting in severe respiratory syndromes are typical symptoms of novel coronavirus. End of the COVID-19 pandemic is unpredictable. In this project, development of vaccine and early diagnosis of the disease is proposed. Currently, there is no proper vaccine for this disease. However, preventive measures are the only solutions for this typical disease. The origin of COVID-19 can be traced back to bat coronavirus, where it is almost to 97% identical to existing strains. However, due to unique furin cleavage site the novel human coronavirus is spreading at alarming rate. This article is discusses the history, classification, characterization and epidemics of viruses especially the coronaviruses.